Interdisciplinary Educational and Physical Activity Interventions as Supportive Care Strategies for Women with Gynecological Cancers: A Comprehensive Review - Długosz, Patrycja; Próchnicka, Magdalena; Nowak, Dominika; Zarzycki, Adam; Noskowicz, Jan; Urban, Jan; Siwek, Michał; Hamouta, Jakub; Konat, Julia; Doroszuk, Wiktor (Quality in Sport, 2025)
Purpose: This review synthesizes current evidence on supportive care strategies aimed at improving the quality of life (QoL) for women undergoing treatment for gynecological cancers. It addresses physical, psychological, and socio-demographic factors influencing outcomes and explores evidence-based interventions, including physical activity, mindfulness, trauma-informed care, and eHealth technologies. Methods: A comprehensive literature review was conducted, examining studies focusing on supportive care interventions, psychological assessment tools, exercise programs, mindfulness techniques, and the influence of socio-demographic variables on health outcomes in women with gynecological cancers. Results: The review highlights the significant burden of gynecological cancers on women’s physical and psychological well-being. Effective supportive care strategies include tailored exercise programs, mindfulness-based interventions, trauma-informed care, and addressing sexual health concerns. Moreover, the importance of customized psychological support, interventions to promote adaptive coping skills, and eHealth approaches is highlighted. The review also identifies the influence of socio-demographic factors such as age, BMI, race/ethnicity, and socio-economic status on access to care and outcomes. Conclusion: This review underscores the need for comprehensive, integrated, and personalized supportive care strategies to enhance the quality of life for women with gynecological cancers. Future research should prioritize large-scale randomized controlled trials, studies on specific populations, and the integration of artificial intelligence and interdisciplinary collaboration to optimize personalized treatment approaches.